MENINGKATKAN KEMANDIRIAN ANAK USIA 5-6 TAHUN MELALUI PEMBELAJARAN METODE PROYEK DI TK PGRI III CANDIWATES PRIGEN - Adinda Meiliatim Putri Trisna Rusdiyanto; Salim, Agus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Project based learning is a learning method that places students at the center of learning. This method also focuses on the process by which the final result of the application of project method learning are obtained in incresing the independence of students aged 5-6 years at the Kindegarten PGRI III Candiwates Prigen. This method greatly influences student activities in class. This type of metode research uses PTK (Classroom Action Research), the background to the selection of this research was to solve problems in a group of subjects who were observed and research and then given further improvement actions according to the situation in the class so that better learningthe study”s findings indicate that children’s independence rises with every cycle. Without action, the precentage of children’s independence during the pre-cycle was only 37,33%, cycle 1 reached 57,66%, and cycle II reached 84,33%. It can be said that the project methodology will increase the independence of kids between the ages of 5-6 years through the poject method at PGRI III CANDIWATES Kindegarten was declared successful.